Association of Polymorphisms Interleukin-10 Gene -819C/T on Susceptibility Systemic Lupus Erythematosus: A Literature ReviewAssociation of Polymorphisms Interleukin-10 Gene -819C/T on Susceptibility Systemic Lupus Erythematosus: A Literature Review - Ade Rizki Putri Ratih; Desi Oktariana; Phey Liana; Yuniza Yuniza (Jurnal Ners, 2026)
Interleukin-10 (IL-10) gene polymorphisms play an important role in influencing individual susceptibility to Systemic Lupus Erythematosus (SLE). Genetic variations in the IL-10 gene can alter mRNA transcription levels and IL-10 protein expression, thereby affecting the balance of immune responses. Increased IL-10 levels are known to enhance B-cell activity and autoantibody production, contributing to immune complex formation and tissue damage characteristic of SLE. Although several studies have shown an association between IL-10 polymorphisms and increased SLE risk, findings vary across populations due to factors such as ethnicity, environmental conditions, and research design. Therefore, this review aims to summarize the existing literature on the association between IL-10 gene polymorphisms and susceptibility to SLE.